Dynamic cluster management and resource utilization using JINI technology - Mahato, Shiva Prasad (Journal of Science and Engineering, 2018)
With the commencement of Electronic Transaction Act, Nepal has taken further step in the field of information and communication technology. With government offices nowadays starting to use computers; there lies ahead many challenges to maximize the utilization of computing resources offered by each computer and minimize the overall cost. With many computers, so many idle resources are being wasted unnecessarily. Jobs can be distributed out to idle servers or even to idle desktops. Many of these resources remain idle during office hours off or even during office hours with many users utilizing the computing as well as memory resources. The proposed model not only utilizes resources to optimum but also makes the architecture more modular, adaptive and then provides dynamic fail over recovery and linear scalability. This approach is useful in a place which requires clusters to set up to perform resource intensive works like data processing or computing works. This model can be realized using JINI/Java Space technology which is open source technology and hence, can be cost effective as compared to other proprietary solutions. The motivating factor of this paper is to understand and identify the architectural constraint in the existing distributed application.